PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI BADAN KEPEGAWAIAN DAN DIKLAT DAERAH KABUPATEN MAMUJU UTARA - Halim, Mahmud (Katalogis, 2016)
This study aims to determine; (1) large simultaneous influence of motivation on employee performance Personnel Board and Regional Training North Mamuju regency; (2) the influence of motivation partially on employee performance Personnel Board and Regional Training North Mamuju regency. The theory of motivation used in this study using the theory of Maslow (1908-1970), namely